2011
DOI: 10.4049/jimmunol.1001675
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphatase Src Homology Region 2 Domain-Containing Phosphatase-1 Is an Intrinsic Central Regulator of Dendritic Cell Function

Abstract: Dendritic cells (DCs) initiate proinflammatory or regulatory T cell responses, depending on their activation state. Despite extensive knowledge of DC-activating signals, the understanding of DC inhibitory signals is relatively limited. We show that Src homology region 2 domain-containing phosphatase-1 (SHP-1) is an important inhibitor of DC signaling, targeting multiple activation pathways. Downstream of TLR4, SHP-1 showed increased interaction with several proteins including IL-1R–associated kinase-4, and mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 61 publications
0
51
2
Order By: Relevance
“…It has been reported that BTLA has two immunoreceptor tyrosine-based inhibitory motifs in the cytoplasmic region and interacts directly with SHP-1 and SHP-2 (SHP-1/2) in T cells (9,11). It has also been reported that SHP-1/2 regulates TLR4 signaling and cytokine production in several cell types (25)(26)(27)(28). To determine whether BTLA regulates TLR4 signaling through the activation of SHP-1/2 in DCs, we first examined SHP-1/2 phosphorylation in BTLA −/− BMDCs and WT BMDCs on LPS stimulation.…”
Section: Btla Inhibits Both Myd88-and Trif-dependent Pathways Of Tlr4mentioning
confidence: 99%
“…It has been reported that BTLA has two immunoreceptor tyrosine-based inhibitory motifs in the cytoplasmic region and interacts directly with SHP-1 and SHP-2 (SHP-1/2) in T cells (9,11). It has also been reported that SHP-1/2 regulates TLR4 signaling and cytokine production in several cell types (25)(26)(27)(28). To determine whether BTLA regulates TLR4 signaling through the activation of SHP-1/2 in DCs, we first examined SHP-1/2 phosphorylation in BTLA −/− BMDCs and WT BMDCs on LPS stimulation.…”
Section: Btla Inhibits Both Myd88-and Trif-dependent Pathways Of Tlr4mentioning
confidence: 99%
“…This finding is consistent with the recent observation that bone marrow-derived macrophages prepared from me v /me v mice manifested marked impairment of LPS-induced IL-12 production (51). In contrast, Ramachandran et al (22) reported that inhibition of Shp1 activity by a specific inhibitor of Shp1 increased the LPS-driven IL-12 production in bone marrowderived DCs. Such difference may be attributable to that we or Zhou et al (51) used isolated splenic DCs from Shp1 CKO mice or bone marrow-derived macrophages from me v /me v mice, respectively, whereas Ramachandran et al (22) used bone marrowderived DCs from wild-type mice.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, Ramachandran et al (22) reported that inhibition of Shp1 activity by a specific inhibitor of Shp1 increased the LPS-driven IL-12 production in bone marrowderived DCs. Such difference may be attributable to that we or Zhou et al (51) used isolated splenic DCs from Shp1 CKO mice or bone marrow-derived macrophages from me v /me v mice, respectively, whereas Ramachandran et al (22) used bone marrowderived DCs from wild-type mice. Thus, the reduced IL-12 production in Shp1 CKO or me v /me v mice may be, in part, an epiphenomenon due to disruption of splenic homeostasis in these mice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This pathway is well described to inhibit macrophage phagocytosis, but more recently, SIRP-α also has been shown to attenuate macrophage activation by LPS by sequestering SHP-2, which is needed for activation of the MAPK and NF-κB pathways (25). In addition, inhibition of SHP-1 in dendritic cells has been reported to enhance CD8 + and CD4 + T-cell responses and reduce regulatory T cells, a response that protected mice against tumor challenge (26). SIRP-α also may negatively regulate cross-presentation by a mechanism not yet understood, perhaps involving recruitment of cross-presentation machinery to phagosomes.…”
Section: Discussionmentioning
confidence: 99%